2004
DOI: 10.1002/ajmg.a.30187
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone deficiency in Costello syndrome

Abstract: We report on three patients with Costello syndrome and isolated growth hormone (GH) deficiency treated with biosynthetic GH. To our knowledge, these are the only patients with Costello syndrome who have been successfully treated for GH deficiency. We review the pathophysiology of Costello syndrome and highlight the recent recommendations of tumor screening and cardiac surveillance in this population, of particular relevance to those receiving GH therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 29 publications
1
25
0
Order By: Relevance
“…As best evidenced in the above‐mentioned cases reports, cutaneous features in patients with Costello syndrome can best be described by the dermatology community as follows: thick loose skin on the dorsal aspects of hands and feet, deep palmar/plantar creases with or without hyperlinearity, curly (but not sparse or fine) hair, focal hyperkeratoses on the extremities and particularly on the hands and feet, acanthosis nigricans (but not diffuse hyperpigmentation), deep‐set and hypoplastic nails, and perinasal and perianal papillomas. The papillomas may also be present around the eyes, mouth, axilla, knee, elbow, and abdomen 4,18 …”
Section: Discussionmentioning
confidence: 99%
“…As best evidenced in the above‐mentioned cases reports, cutaneous features in patients with Costello syndrome can best be described by the dermatology community as follows: thick loose skin on the dorsal aspects of hands and feet, deep palmar/plantar creases with or without hyperlinearity, curly (but not sparse or fine) hair, focal hyperkeratoses on the extremities and particularly on the hands and feet, acanthosis nigricans (but not diffuse hyperpigmentation), deep‐set and hypoplastic nails, and perinasal and perianal papillomas. The papillomas may also be present around the eyes, mouth, axilla, knee, elbow, and abdomen 4,18 …”
Section: Discussionmentioning
confidence: 99%
“… 1 Costello et al ., 1977 and Costello et al ., 1996; Der Kaloustian et al ., 1991; Martin and Jones, 1991; Borochowitz et al ., 1992; Teebi et al ., 1993; DiRocco et al ., 1993; Izumikawa et al .,1993; Kondo et al .,1993; Patton et al ., 1993; Phillip and Mancini, 1993; Zampino et al ., 1993; Say et al ., 1993; Yoshida et al ., 1993; Davies et al ., 1994; Okamoto et al ., 1994; Fryns et al ., 1994; Torres et al, 1994; Umans et al ., 1994; Torrelo et al, 1995; Mori et al ., 1996; Fukao et al ., 1996; Johnson et al ., 1998; Pratesi et al ., 1998; Tomita et al, 1998; Siwik et al ., 1998; Franceshini et al, 1999; Szalai et al , 1999; van Eeghen et al, 1999; Bisogno et al ., 1999; Innes and Chudley, 2000; Moroni et al ., 2000; Sigaudy et al ., 2000; Hatamochi et al ., 2000; Boente et al, 2001; Gripp et al, 2002; Kaji et al ., 2002; Kamoda et al ., 2002; van den Bosch et al ., 2002; Urakami et al ., 2002; Kawame et al, 2003; Delrue et al, 2003; Mancini et al ., 2003; DiRocco et al ., 2003; Nasca et al, 2003; Cakir et al ., 2004; Waldburg et al ., 2004; Dickson et al, 2004; Gregersen et al ., 2004; Stein et al, 04; Hinek et al, 2005; Alexander et al ., 2005; White et al ., 2005. 2 Lin et al ., 2008 represented the compilation of Gripp et al ., 2006 and Estep et al, 2006; Kerr et al ., 2006; Steens et al, 2006; Zampino et al, 2006; Digilio et al ., 2007; Limongelli et al ., 2007; Denayer et al ., 2007; Lo et al ., 2008; Hou et al ., 2008; Gripp et al, 2008. 3 Case reports in the literature who were later included in extensive reviews were generally reported only in Group II, e.g. patients 1 and 3 in Zampino et al , 1993 were also patients CS-01 and CS-04 in Zampino et al, 2006).…”
Section: Figurementioning
confidence: 99%
“…Each of these physical traumas can lead to inadequate GH production from the hypothalamus or the pituitary gland. Tumors may also cause insufficient secretion of one or more hormones and lead to GHD (Bogarin and Steinbok 2009;Stein et al 2004).…”
Section: Introductionmentioning
confidence: 99%